LYMPHATIC FILARIASIS DRUG TREATMENT POLICIES IN EASTERN INDONESIA: WHAT TARGET CHARACTERISTICS MATTER? - Kesuma, Agung Puja; Ipa, Mara; Laksono, Agung Dwi; Wahono, Tri; Marina , Rina; Hakim, Lukman (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: Lymphatic filariasis (LF) drug treatment compliance remains a challenge in Eastern Indonesia. Aims: The study sought to determine which aspects of Eastern Indonesia's LF drug treatment compliance policies were most pertinent. Methods: The 2018 Indonesian Basic Health Survey data was employed. The analysis units were adults (â‰¥ 15 years) who had received LF drug treatment. LF drug treatment compliance was analyzed based on respondent characteristics (age, gender, marital status, education, occupation, wealth and comorbidities) using binary logistic regression. Results: The proportion of adherence to LF treatment in Eastern Indonesia was 73.1%. Respondent characteristics that influenced LF treatment compliance were age group > 24 (aOR = 1.374, 95% CI: 1.305-1.447), female (aOR = 1.307, 95% CI: 1.263-1.353), all educated respondent status (aOR = 2.152, 95% CI: 2.043-2.268), and all employed respondents (aOR = 1.437, 95% CI: 1.365 - 1.512). Married respondents and those with all levels of wealth status were less likely to take LF drug treatment. Conclusion: Policy focus on improving LF treatment compliance among the younger male, the less educated, the unemployed, and those with lower social economic status. Keywords: compliance, Eastern Indonesia, lymphatic filariasis, public health